2017
DOI: 10.1017/s0144686x17000952
|View full text |Cite
|
Sign up to set email alerts
|

Dementia in rural settings: examining the experiences of former partners in care

Abstract: Informal carers, also referred to as partners in care, provide the bulk of care to people living with dementia across a range of community settings; however, the changing experiences and contexts of providing informal care for people with dementia in rural settings are under-studied. Drawing on 27 semi-structured interviews with former partners in care in Southwestern and Northern Ontario, Canada, we examine experiences of providing and accessing care over the course of the condition and across various setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…Northern Norway is characterized by large geographical areas with dispersed populations that may complicate an effective provision of services. Previous studies have demonstrated that the needs of rural families are not met by the community healthcare services due to restricted hours and limited availability (Herron & Rosenberg, 2017; Morgan, Semchuk, Stewart, & D’Arcy, 2002) or inappropriate deliveries of the services (Innes, Blackstock, Mason, Smith, & Cox, 2005). Rural caregivers may receive more support from other family members (Ehrlich, Bostrom, Mazaheri, Heikkila, & Emami, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Northern Norway is characterized by large geographical areas with dispersed populations that may complicate an effective provision of services. Previous studies have demonstrated that the needs of rural families are not met by the community healthcare services due to restricted hours and limited availability (Herron & Rosenberg, 2017; Morgan, Semchuk, Stewart, & D’Arcy, 2002) or inappropriate deliveries of the services (Innes, Blackstock, Mason, Smith, & Cox, 2005). Rural caregivers may receive more support from other family members (Ehrlich, Bostrom, Mazaheri, Heikkila, & Emami, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Studies were primarily conducted in Canada (Hawranik & Strain, 2001;Herron & Rosenberg, 2019a, 2019bMorgan et al, 2002), the Netherlands (Boots et al, 2015;Wolfs et al, 2010Wolfs et al, , 2012, the UK (Durand et al, 2009;Herat-Gunaratne et al, 2020;Kaisey et al, 2012), Australia (Low et al, 2015;Macleod et al, 2017;Xiao et al, 2015) and the USA (Gitlin et al, 2010;Jablonski et al, 2019).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Key themes included the need for care professionals to provide a clear overview of the services available and regularly revisit and review these as individuals' and families' needs changed (Macleod et al, 2017;Morgan et al, 2002;Stephan et al, 2018;Wolfs et al, 2010Wolfs et al, , 2012. Sharing learning from other caregivers (Herron & Rosenberg, 2019a;Morgan et al, 2002;Wolfs et al, 2012), offering advice and anticipating transitions in care (enabling people to plan in advance) were also seen as important (Wolfs et al, 2010(Wolfs et al, , 2012, as was empowering service users and caregivers to make their own decisions (Macleod et al, 2017;Morgan et al, 2002;Stephan et al, 2018;Wolfs et al, 2010Wolfs et al, , 2012. Providing family caregivers with disease-specific knowledge (Boots et al, 2015;Morgan et al, 2002;Stephan et al, 2018;Xiao et al, 2015), and specialist support (including counselling and/or help to overcome their own reluctance to accept assistance) (Herron & Rosenberg, 2019a;Morgan et al, 2002;O'Shea et al, 2019;Rapaport et al, 2020;Stephan et al, 2018;Wolfs et al, 2010) were also perceived to be helpful.…”
Section: Wider Attempts To Increase the Uptake Of Services By Older P...mentioning
confidence: 99%
“…More novel is a perspective that has emerged on seasonality, focused on the challenges of weather for caregivers at different times of the year (Joseph et al., 2013; Skinner et al., 2009) and on the (health) care challenges of seasonal migration (Pickering et al., 2020). On the other hand, the care literature also deals with shorter timeframes and more intimate scales, such as in considerations of quickly changing care pathways and situations (Herron & Rosenberg, 2019; Vrotsou et al., 2017), in considerations of the time–space dimensions of caring practice or ‘carescapes’ (Bowlby, 2012; Herron & Skinner, 2012), and in its specific consideration of the introductory and meaningful experiences of waiting rooms in healthcare facilities, including the importance of design, decorative and interpersonal features (Eggleton et al, 2017; Evans et al., 2009; Kearns et al., 2020). These latter studies complement other research reviewed later on the affective, embodied experience of waiting.…”
Section: Relative/conscious Time (Knowing Time)mentioning
confidence: 99%